Optimization of disulfide mapping using mass spectrometry - Matsumiya, Nozomi (Kansas State University, 2009)
One of the important keys to characterize the biological function of a protein is the study of post-translational modification (PTM). Formation of disulfide bond linkages between cysteine residues within a protein is a common PTM which not only contributes to folding and stabilizing the protein structure, but also to accomplishing its native function. Therefore, the study and discovery of structural-functional relationships of expressed proteins using an isolated proteomics approach has been one of the biggest advances within the field of structural biology in recent years. In this study, rapid disulfide bond mapping of freshly obtained equine serum albumin (ESA) was performed using matrix assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS). Highly sensitive MALDI-TOF MS is commonly used for the investigation of disulfide bond linkages in the proteomics field. However, it has also been known that the presence of disulfide bond linkages absorbs the energy which is created by the cysteine-cysteine kinetic vibration, resulting in a decrease of the instrumental sensitivity. To overcome this problem, the disulfide bond mapping method was optimized by applying a combination of chemical labeling, proteolytic enzymes, and matrices. With the optimized method, we were also able to achieve high protein sequence coverage. Obtaining higher sequence coverage of a protein provides more information about a protein which helps to identify the protein by peptide mass fingerprint (PMF) technique. These analyses eventually contribute to the estimation of the possible PTM sites.
Keywords: Disulfide bond mapping; Mass spectrometry; Post translational modification (PTM); Proteomics; Chemistry, Biochemistry (0487)